Financial Crises and Monetary Expansion - Ola Honningdal Grytten (Norges Bank, 2011)
On the basis of data from the Historical Monetary Statistics-project by Norges Bank, the present paper serves a threefold purpose. In the first place it gives an overview of financial crisis in Norway from her independence from Denmark in 1814 till present times. Secondly, historical business cycles are mapped and we conclude that the major financial crises were mirrored in significant slumps in the real economy. Thirdly, the paper investigates credit and monetary developments, and concludes that the major financial crises in Norway typically took place after substantial money and credit expansion causing overheating and bubbles to the economy.
hdl:11250/2496938
Keywords: E32; E51; G01; N13; N14; 330; business cycles; supply of money and credit; financial crisis